2015
DOI: 10.1038/mp.2015.165
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study identifies SESTD1 as a novel risk gene for lithium-responsive bipolar disorder

Abstract: Lithium is the mainstay prophylactic treatment for bipolar disorder (BD), but treatment response varies considerably across individuals. Patients who respond well to lithium treatment might represent a relatively homogeneous subtype of this genetically and phenotypically diverse disorder. Here, we performed genome-wide association studies (GWAS) to identify (i) specific genetic variations influencing lithium response and (ii) genetic variants associated with risk for lithium-responsive BD. Patients with BD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 74 publications
1
57
2
1
Order By: Relevance
“…With regard to noncanonical Wnt signaling in BD, a recent large GWAS study identified a single locus containing a noncoding SNP with strong linkage to lithium-responsive BD: SEC14 and spectrin domain containing 1 (SESTD1) [305]. Sestd1, expressed both during neurodevelopment and in the mature CNS [306], has recently been shown to directly interact with Dvl2, Dact1, and Vangl2 in a PCP-related signaling cascade during embryonic development [307].…”
Section: Human Genomic Studiesmentioning
confidence: 99%
“…With regard to noncanonical Wnt signaling in BD, a recent large GWAS study identified a single locus containing a noncoding SNP with strong linkage to lithium-responsive BD: SEC14 and spectrin domain containing 1 (SESTD1) [305]. Sestd1, expressed both during neurodevelopment and in the mature CNS [306], has recently been shown to directly interact with Dvl2, Dact1, and Vangl2 in a PCP-related signaling cascade during embryonic development [307].…”
Section: Human Genomic Studiesmentioning
confidence: 99%
“…Another recent GWAS from Sweden and the United Kingdom was performed on over 2698 patients with subjectively defi ned (self-reported) lithium response and 1176 patients with objectively defi ned (clinically documented) lithium response and compared with a group of healthy controls (Song et al 2015 ). When comparing lithium-responsive patients with controls, two imputed markers revealed genomewide signifi cant associations, one of which was validated in confi rmatory genotyping.…”
Section: Pharmacogenetics Of Lithiummentioning
confidence: 99%
“…When comparing lithium-responsive patients with controls, two imputed markers revealed genomewide signifi cant associations, one of which was validated in confi rmatory genotyping. These two genetic markers are an intronic single nucleotide polymorphism (SNP) on chromosome 2q31.2 in gene SEC14 and spectrin domains 1 (SESTD1), which encodes a protein involved in regulating phospholipids (Song et al 2015 ). Phospholipids have been strongly implicated as lithium treatment targets.…”
Section: Pharmacogenetics Of Lithiummentioning
confidence: 99%
“…In the past few years, genome-wide association studies suggested several genetic variants associated with lithium response [Chen et al, 2014;Perlis et al, 2009;Song et al, 2015;Squassina et al, 2011]. However, it must be noted that most of these studies were limited by small sample size.…”
Section: Pharmacogenetics Of Lithium Responsementioning
confidence: 99%
“…Interestingly, dysfunction of emotional processing has been observed in BPD [Rock et al, 2010] and a number of emotional processing tasks have been proposed as potential surrogate markers of response in mood disorders [Harmer et al, 2011]. Specifically, ebselen decreased reward reinforcement during the reward and punishment learning task [Song et al, 2015] and increased recognition of emotional facial expressions during the emotional processing tasks [Masaki et al, 2016;Song et al, 2015]. Similarly to lithium [Adida et al, 2015], ebselen can reduce impulsivity [Masaki et al, 2016].…”
Section: The Promise Of New Interventions: the Case Of Ebselenmentioning
confidence: 99%